Education and Prosocial Behavior: Evidence from Time Use Survey - Betul Akar; Pelin Akyol; Cagla Okten (Institute of Labor Economics (IZA), 2019)
We use the extension of compulsory education from five to eight years in Turkey as an instrument for educational attainment to investigate the causal effects of education on prosocial behavior by utilizing Turkish Time Use Survey data. Ours is the first paper that investigates the causal effect of education on volunteering. We find that the education reform increased the education levels significantly, and increased education had a causal negative and significant impact on prosocial behavior of men as time spent in volunteering and helping others decreased. We also investigate the causal channels through which education decreases prosocial behavior. We find that schooling increased the likelihood of earning higher wages and work hours, which suggests that men substituted hours worked for time spent in prosocial activity as a result of an exogenous increase in their education levels. Our findings also suggest that education might have enhanced individualism and self-centrism as we find that time spent in leisure and sport activity increased. We do not find any significant effects of education on female prosocial behavior in Turkey, where female labor force participation rate at 32 percent has remained low and stagnant across the years.
Keywords: I21; I26; D01; D64; 330; prosocial behavior; volunteering; helping; education; externalities